Chlorophyll-Mediated Changes in the Redox Status of Pancreatic Cancer Cells Are Associated with Its Anticancer Effects - Vaňková, Kateřina; Marková, Ivana; Jašprová, Jana; Dvořák, Aleš; Subhanová, Iva; Zelenka, Jaroslav; Novosádová, Iva; Rasl, Jan; Vomastek, Tomáš; Sobotka, Roman; Muchová, Lucie; Vítek, Libor (Oxidative medicine and cellular longevity, 2018)
Nutritional factors which exhibit antioxidant properties, such as those contained in green plants, may be protective against cancer. Chlorophyll and other tetrapyrrolic compounds which are structurally related to heme and bilirubin (a bile pigment with antioxidant activity) are among those molecules which are purportedly responsible for these effects. Therefore, the aim of our study was to assess both the antiproliferative and antioxidative effects of chlorophylls (chlorophyll a/b, chlorophyllin, and pheophytin a) in experimental pancreatic cancer. Chlorophylls have been shown to produce antiproliferative effects in pancreatic cancer cell lines (PaTu-8902, MiaPaCa-2, and BxPC-3) in a dose-dependent manner (10-125 μmol/L). Chlorophylls also have been observed to inhibit heme oxygenase (HMOX) mRNA expression and HMOX enzymatic activity, substantially affecting the redox environment of pancreatic cancer cells, including the production of mitochondrial/whole-cell reactive oxygen species, and alter the ratio of reduced-to-oxidized glutathione. Importantly, chlorophyll-mediated suppression of pancreatic cancer cell viability has been replicated in in vivo experiments, where the administration of chlorophyll a resulted in the significant reduction of pancreatic tumor size in xenotransplanted nude mice. In conclusion, this data suggests that chlorophyll-mediated changes on the redox status of pancreatic cancer cells might be responsible for their antiproliferative and anticancer effects and thus contribute to the decreased incidence of cancer among individuals who consume green vegetables.
Keywords: nádorové buněčné linie; Real-Time Polymerase Chain Reaction; chlorofyl; mitochondrie; Antioxidants; Glutathione; nádory slinivky břišní; peroxid vodíku; superoxidy; Cell Line, Tumor; Oxidation-Reduction; Antineoplastic Agents; Glutathione Disulfide; kvantitativní polymerázová řetězová reakce; antioxidancia; Extracellular Signal-Regulated MAP Kinases; protinádorové látky; Humans; feofytiny; glutathion; Pancreatic Neoplasms; Chlorophyll; Heme Oxygenase (Decyclizing); viabilita buněk; Cell Survival; hemová oxygenasa (decyklizující); Superoxides; extracelulárním signálem regulované MAP kinasy; Mitochondria; oxidace-redukce; Synechocystis; glutathiondisulfid; Hydrogen Peroxide; Pheophytins; lidé